Obesity and energy balance: What is the role of physical activity?. Issue 6 (1st November 2016) - Shook, Robin P.
ABSTRACT: Introduction : Despite billions of dollars spent over decades of research, debate remains over the causes and solutions of the obesity epidemic. The specific role of physical activity in the prevention or treatment of obesity seems a particularly contentious issue, with opposing views put forth in both academic and popular media. In an attempt to provide context and clarity to the specific question of the role of physical activity in determination of body weight, we have attempted to identify evidence or lack thereof in the scientific literature and provide a summary of our findings. Areas covered : Topics included in this narrative review are an overview of energy balance, the relationship between physical activity and energy expenditure, compensatory responses in non-exercise energy expenditure and energy intake, and the relationship between physical activity and obesity. Expert commentary : Based on a review of the existing literature, daily physical activity and structured exercise has beneficial effects on an individual's body weight. In most instances, exercise occurring in adequate amounts will increase total daily energy expenditure and create an acute energy deficit, without compensatory decreases in non-exercise physical activity or energy expenditure nor compensatory increases in energy intake. Several gaps in the literature exist, both in terms of the number of adequately powered clinical trials with rigorous assessments of both energy intake and expenditure, and with a variety of study populations (by age, sex, race, etc.) and with varying exercise volumes and intensities.